STRATEGI PENGEMBANGAN USAHA EKSPEDISI CV. RAJAWALI ANDALAN PRATAMA SLEMAN - Candra, Elvira Puspita; Sayekti, Lulu Anastesi (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
This research is a descriptive qualitative study that aims to know the development strategy of the CV. Rajawali Andalan Pratama Sleman with a swot analysis. Technology development has become a factor in changing the power to buy people from offline to online, this makes the expedition service very appealing to the public because through the services of the expedition the goods will be delivered to a place where the people want it to go. That's why expedition services competition has become increasingly intense and every expedition service company has to be able to devise a strategy to deal with the competition. Besides, the whole point of this research is to find strategies that has never done before CV. Rajawali Andalan Pratama Sleman. Prescription research contains a discussion on CV. Rajawali Andalan Pratama using internal and external indicators to find strength, Weakness., Chances and threats., and there is an analysis of the swot matrix.Keyword: Strategy; Internal Indicators; External Indicators; SWOT Matrix.